SISTEM INFORMASI PENGGAJIAN (PAYROLL) KARYAWAN MENGGUNAKAN METODE NETTO BERBASIS WEB PADA D'SOCCER UNGARAN FOOTBALL STADIUM - Tantik Sumarlin; Bambang Widjanarko Susilo; Febryantahanuji Febryantahanuji (Jurnal Akuntansi dan Bisnis, 2024)
This research aims to explore a web-based payroll information system. The location of the research is at D'Soccer Ungaran Football Stadium, a mini soccer field rental business. From observations, several risks were found in salary management, including: 1) The risk of salary calculation errors due to conventional methods. 2) Risk of corruption and data loss because there is no database yet. 3) Employee salary reports are still prepared manually, less efficient. Based on this problem, the author designed a payroll system with a net method for withholding income tax 21. The use of this method aims to help employees reduce dissatisfaction due to tax deductions. The results of the effectiveness test showed that the new system was more effective than the old system, with a score ratio of 11:20 and performance effectiveness of 44%:80%.